2018
DOI: 10.1139/cgj-2017-0594
|View full text |Cite
|
Sign up to set email alerts
|

Field performance of a peat railway subgrade reinforced with helical screw piles

Abstract: Rail tracks on peat subgrades can experience significant deflections, some of which have led to derailments. A potential ground stabilization strategy is to use screw piles to reduce rail displacements; however, limited research has been undertaken to investigate the effect of these piles and their performance under cyclic train loading. A field site was instrumented and monitored before and after screw pile installation. The piles were instrumented with strain gauges, piezometers were installed in the peat, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Due to the limited results available, no relationship could be established between the pile's orientation and the amount of axial load borne. On the basis of the monitoring data at this location, it appeared that the expected load transfer from the ties to the piles by arching within the ballast layer was not accomplished [121].…”
Section: Selected Applications In Practice and Challenges Facedmentioning
confidence: 96%
See 1 more Smart Citation
“…Due to the limited results available, no relationship could be established between the pile's orientation and the amount of axial load borne. On the basis of the monitoring data at this location, it appeared that the expected load transfer from the ties to the piles by arching within the ballast layer was not accomplished [121].…”
Section: Selected Applications In Practice and Challenges Facedmentioning
confidence: 96%
“…This research showed that it is possible to refine a pre-designed reinforcement solution and verify the feasibility and design approach of the piling technique using full-scale experimentation. Wheeler et al [121] evaluated the field performance of helical screw pile-supported peat railway subgrade located on the CN Rail Lévis subdivision in southeastern Quebec. The piles were mounted with strain gauges to determine the corresponding axial strains, piezometers were placed in the peat to monitor static and dynamic pore water pressures before and after installation of the piles, and track and subgrade displacements were measured using high-speed cameras before and after installation of the piles.…”
Section: Selected Applications In Practice and Challenges Facedmentioning
confidence: 99%
“…In another field study, Cannon conducted dynamic loading tests on helical piles of different sizes and lengths under different ground conditions [162]. Also, several recent works were conducted by Wheeler amount of rail displacement due to the passage of the train [213]. Elkasabgy and Naggar studied the effect of lateral vibration on helical piles in clay [217].…”
Section: The Loading Typementioning
confidence: 99%
“…For example, Digital Image Correlation (DIC) techniques have been successfully applied to measure track displacements at the locations of high-quality subgrade, poor quality subgrade, and track transitions in order to gain an improved understanding of how the monitored tracks behaved. 4,1317 Additionally, Rayleigh backscatter-based distributed fiber optic strain sensors have been successfully used to measure rail strains at a sampling rate and spatial resolution that permitted the calculation of rail stresses, rail deflection profiles, and rail seat forces for several consecutive sleepers. 18,19…”
Section: Introductionmentioning
confidence: 99%
“…More recently, DIC has been used in conjunction with a system of synchronized high-speed cameras to measure vertical displacements of rails, sleepers, and ballast, as well as longitudinal displacements of rails with sub-pixel accuracy. 1517,21…”
Section: Introductionmentioning
confidence: 99%